Efektivitas Pengawetan dengan Terusi (CuSO4) terhadap Peningkatan Kelas Awet Tiga Jenis Kayu Lokal Maluku Utara - M. Syaikhan Amran; Aisjah Rachmawaty Ryadin; Adesna Fatrawana (Universitas Khairun, 2026)
Marfala wood, Matoa wood, and Gosale wood are types of wood that are often used and traded in North Maluku as the main building materials and furniture. Wood preservation aims to increase the service life of the wood, prevent pests and diseases, and reduce the risk of structural damage. One of the wood preservation methods used in this study is using Copper Sulfate (CuSO4) or terusi. The purpose of this study was to analyze the effect of copper sulfate or terusi on the durability of three types of local North Maluku wood against subterranean termite attacks. This study was conducted for 1 week in the Laboratory of the Faculty of Agriculture and for 3 months for termite tests in the garden land of Gamayou Village. The results of the study were then analyzed by calculating the average weight loss value, then the percentage of weight loss and wood resistance to termite attacks were then compared with standards referring to SNI 01-7207-2006. The results of the study showed that the average weight loss of marfala, matoa, and gosale wood without preservatives and with preservatives was (3.90% & 0.86%), (13.99% & 3.83%) and (12.12% & 3.23%), respectively. Based on these results, there was an increase in the durability class of the three types of wood from class IV to class II for matoa and from clas IV to I gosale wood, and from class II to class I for marfala wood. Keywords: CuSO4, Gosale, Marfala, Matoa, Preservative.